Ablation of the cardiac-specific gene leucine-rich repeat containing 10 (Lrrc10) results in dilated cardiomyopathy. - Matthew J Brody; Timothy A Hacker; Jitandrakumar R Patel; Li Feng; Junichi Sadoshima; Sergei G Tevosian; Ravi C Balijepalli; Richard L Moss; Youngsook Lee (PLoS ONE, 2012)
Leucine-rich repeat containing 10 (LRRC10) is a cardiac-specific protein exclusively expressed in embryonic and adult cardiomyocytes. However, the role of LRRC10 in mammalian cardiac physiology remains unknown. To determine if LRRC10 is critical for cardiac function, Lrrc10-null (Lrrc10(-/-)) mice were analyzed. Lrrc10(-) (/-) mice exhibit prenatal systolic dysfunction and dilated cardiomyopathy in postnatal life. Importantly, Lrrc10(-/-) mice have diminished cardiac performance in utero, prior to ventricular dilation observed in young adults. We demonstrate that LRRC10 endogenously interacts with α-actinin and α-actin in the heart and all actin isoforms in vitro. Gene expression profiling of embryonic Lrrc10(-/-) hearts identified pathways and transcripts involved in regulation of the actin cytoskeleton to be significantly upregulated, implicating dysregulation of the actin cytoskeleton as an early defective molecular signal in the absence of LRRC10. In contrast, microarray analyses of adult Lrrc10(-/-) hearts identified upregulation of oxidative phosphorylation and cardiac muscle contraction pathways during the progression of dilated cardiomyopathy. Analyses of hypertrophic signal transduction pathways indicate increased active forms of Akt and PKCε in adult Lrrc10(-/-) hearts. Taken together, our data demonstrate that LRRC10 is essential for proper mammalian cardiac function. We identify Lrrc10 as a novel dilated cardiomyopathy candidate gene and the Lrrc10(-/-) mouse model as a unique system to investigate pediatric cardiomyopathy.